PENDAMPINGAN LEGALITAS USAHA DAN KUALITAS PRODUK USAHA MIKRO KECIL MENENGAH PENDUKUNG SEKTOR KEPARIWISATAAN DESA LALIKO - Basri Basri; Naim Irmayani; Muhammad Assidiq; Indrabayu Indrabayu; Jalaluddin Jalaluddin; Hamzah Hamzah; Muskira Sudirman; Nur Cahya; Fadliah Fadliah; Nur Amelia (Universitas Mataram, 2023)
Strengthening the tourism sector village tourism sector, in addition to attractions, it is very necessary to also get the support of Micro, Small and Medium Enterprises (MSMEs) products as souvenirs and economic drivers of the community. around tourist sites. The results of observations show that home-scale micro-business groups Micro-scale business groups, which currently do not receive intensive assistance. Though based on initial observations, this is very potential, given the efforts to strengthen the tourism sector. Tourism sector is being carried out by the village government. The purpose of this activity This activity aims to assist the strengthening of MSMEs in terms of, institutionalization, business legality, as well as business assistance in terms of packaging and labeling and business branding. and business branding. Assistance is carried out for 4 months of activities starting from from situation analysis to implementation with the concept of empowerment. showed that the community groups were enthusiastic about participating in the activities and there was an increase in product quality. improvement in product quality. In addition, there were 8 groups that had not previously received business assistance with this activity, the MSME group has a registered business and receives assistance. group has a registered business and receives assistance in terms of improving product quality, providing packaging, and labeling.